2022
DOI: 10.3389/fgene.2022.668696
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Model of Eleven Genes Based on the Immune Microenvironment in Patients With Thymoma

Abstract: Purpose: The pathogenesis of thymoma (THYM) remains unclear, and there is no uniform measurement standard for the complexity of THYM derived from different thymic epithelial cells. Consequently, it is necessary to develop novel biomarkers of prognosis estimation for patients with THYM.Methods: Consensus clustering and single-sample gene-set enrichment analysis were used to divide THYM samples into different immunotypes. Differentially expressed genes (DEGs) between those immunotypes were used to do the Kyoto E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…The immunotype B group consisted of more immune factors, such as macrophages, NK cells, Treg, Type II IFN response, and aDCs, compared to the immunotype A group. Furthermore, the survival analysis revealed that the immunotype A group resulted in significantly better survival [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The immunotype B group consisted of more immune factors, such as macrophages, NK cells, Treg, Type II IFN response, and aDCs, compared to the immunotype A group. Furthermore, the survival analysis revealed that the immunotype A group resulted in significantly better survival [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Te expression level of UGT3A2 is related to DNA methylation and afects the occurrence and development of LAML [43]. An 11-gene signature, including UGT3A2, established based on the immune microenvironment can be employed for the prediction of the prognosis of thymoma patients [44]. BLOCK1S1, also known as GCN5L1, is a new molecule homologous to the sequence of nuclear acetyltransferase GCN5, which is involved in the regulation of mitochondrial autophagy, fatty acid oxidation, and other mitochondrial biological processes [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation or mutation of genes encoding proteins essential for highfidelity DNA replication is often associated with disease, particularly cancer [17]. The histone genes are involved in chromatin organisation which is essential for the regulation of gene expression and DNA replication [18].…”
Section: Identification Of Histone Genes Involved In Negative Regulat...mentioning
confidence: 99%
“…During cell division, chromatin condenses into chromosomes which can be separated into two daughter cells. Dysregulation of histone genes can lead to abnormal chromosome segregation during cell division [18]. In addition to their role in DNA replication and cell division, histones also play a role in regulating gene expression.…”
Section: Identification Of Histone Genes Involved In Negative Regulat...mentioning
confidence: 99%
See 1 more Smart Citation